2020
DOI: 10.1016/j.hpb.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio as a prognostic marker in metastatic gallbladder cancer

Abstract: Background: Neutrophil-to-lymphocyte ratio (NLR) has been used as an inflammation based prognostic marker for various malignancies. This study evaluated the association between NLR and overall survival (OS) in patients with metastatic gallbladder cancer (GBC) Methods: An optimal cut off point for NLR was identified by plotting spline-based hazard ratio curves to identify a threshold effect and patients were divided into two groups, 5 or <5. Kaplan-Meier curves were plotted for NLR5 and NLR<5 and OS between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…After removal of duplicates, we browsed the titles and abstracts of the remaining 134 studies, and 107 studies were excluded according to the inclusion and exclusion criteria. Then we assessed full-text review of the remaining 27 studies, another 13 studies were excluded and finally 14 retrospective cohort studies were included for meta-analysis (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Basic characteristics of included studies were listed in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of duplicates, we browsed the titles and abstracts of the remaining 134 studies, and 107 studies were excluded according to the inclusion and exclusion criteria. Then we assessed full-text review of the remaining 27 studies, another 13 studies were excluded and finally 14 retrospective cohort studies were included for meta-analysis (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Basic characteristics of included studies were listed in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Despite the robust and growing data regarding the utility of these WBCC-derived indexes, findings are not uniform across all publications. Furthermore, previous studies mainly focused on colorectal, pancreatic, prostate, lung, esophageal-gastric and breast cancers (7), only few studies conducted investigations on GBC until recently (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Based on the available data, we aimed to systematically review and rationalize the evidence for the prognostic value of these WBCC-derived indexes in predicting outcomes of GBC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The medical centres covered by this study did not routinely analyse whole differential white blood cell counts, making it impossible to perform calculations on NLR, which previously have been shown to be a prognostic marker for both OS and PFS [ 24 , 25 , 26 ]. Some studies have however investigated the use of dNLR and found it to be a reasonable surrogate for NLR [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…
We recently read with great interest the article by Mady et al titled 'Neutrophil to lymphocyte ratio as a prognostic marker in metastatic gallbladder cancer' . 1 In that article the authors aimed to evaluate the association between NLR and overall survival in patients with metastatic gallbladder cancer. The authors determined that NLR is an independent predictor of poor prognosis in patients with metastatic GBC.
…”
mentioning
confidence: 99%